Lipoleiomyoma of the Uterus and Primary Ovarian Leiomyoma in a Postmenopausal Woman: Two Rare Entities in the Same Individual - Sefa Kelekci; Serenat Eris; Emine Demirel; Serpil Aydogmus; Nese Ekinci (Case Reports in Pathology)
Uterine lipoleiomyomas are rare benign tumours that are composed of various mixtures of smooth muscle and mature fat tissue. Leiomyomas, which arise primarily in the ovary, are extremely rare tumours that account for 0.5–1% of all benign ovarian tumours. To the best of our knowledge, we present the first case of an ovarian leiomyoma coexisting with a uterine lipoleiomyoma in the postmenopausal period. A 59-year-old, gravida 4, para 3, postmenopausal woman exhibited pelvic discomfort and increased frequency of micturition. A pelvic examination revealed a solid, tender mass on the left side that could not be clearly separated from the uterus. She underwent a laparotomy with an initial diagnosis of a left ovarian mass. She had previously undergone a total abdominal hysterectomy and bilateral salpingo-oophorectomy. A histopathological examination revealed a uterine lipoleiomyoma, composed of variable amounts of smooth muscle cells and mature adipocytes and a right ovarian leiomyoma composed of interlacing bundles and fascicles of spindle cells. The coexistence of these two rare entities in the same individual may represent a common pathway as a stimulating agent. This case may help to clarify the pathogenesis of these lesions.